PENDAMPINGAN PENGELOLAAN PENYEDIAAN AIR BERSIH MASYARAKAT DUSUN MUJO DESA SUMOGAWE KABUPATEN SEMARANG - Tutuko, Bambang; Wanto, Sri; Purwanto, Purwanto; Kustirini, Anik (LPPM Universitas Bina Bangsa, 2025)
In Mujo Hamlet, Sumogawe Village, Getasan District, there has been no effort to organize an institutional clean water supply program. So far, the community has held it independently, either individually or in groups of around five heads of families. The aim of this community service activity is to form an organizing institution for the management of clean water supply for the community and to create an initial design for the distribution of clean water networks to residents' homes. The implementation method begins with a location survey, outreach and audience with the community, monitoring and evaluation. The results of this activity are maps of the distribution of clean water pipe networks from springs to people's homes. By having a map of the distribution of clean water pipe networks, it is hoped that the community will participate together in forming an institution that organizes clean water supply and can carry out its implementation well.